2010
DOI: 10.1111/j.1365-277x.2009.01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dietitians’ nutrition counselling self‐efficacy and its positive relationship with reported skill usage

Abstract: Background-Previous studies on nutrition counselling self-efficacy assessed small groups of dietitians in focused practice areas or evaluated the effectiveness of skills training on only a few skills. This descriptive study developed a comprehensive scale to examine self-efficacy in a large, cross-sectional sample of practising dietitians in performing various counselling skills that promote dietary behaviour changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 35 publications
3
31
0
1
Order By: Relevance
“…A patient-centred, counselling approach is seen as an essential element of dietetic practice (Gable, 2007), although there is not universal understanding of the concept amongst dietitians (MacLellan & Berenbaum, 2006). In addition, although there is evidence that dietitians perceive themselves to be effective in using counselling skills, this has not yet been related to their actual counselling performance (Lu & Dollahite, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A patient-centred, counselling approach is seen as an essential element of dietetic practice (Gable, 2007), although there is not universal understanding of the concept amongst dietitians (MacLellan & Berenbaum, 2006). In addition, although there is evidence that dietitians perceive themselves to be effective in using counselling skills, this has not yet been related to their actual counselling performance (Lu & Dollahite, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, including the present one, have indicated a deficit in communication skills training throughout university . Current dietetic curriculums do place a larger emphasis on communication skills to complement the teaching of nutrition science .…”
Section: Discussionmentioning
confidence: 62%
“…Assessments into the self‐efficacy of nutrition counselling skills of dietitians have reported a lack of training and confidence in the use of behaviour change techniques (Whitehead et al . ; Lu & Dollahite ). Thus, highlighting the importance of developing these skills.…”
Section: Discussionmentioning
confidence: 99%